SAT0083 Ultrasonography Changes Correlate with Pro-Inflammatory Cytokines Levels in Patients with Early Rheumatoid Arthritis. (9th June 2015) - Alekseeva, O.; Severinova, M.; Pushkova, O.; Avdeeva, A.; Aleksandrova, E.; Novikov, A.; Luchikhina, E.; Karateev, D.; Volkov, A.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by joint swelling, joint tenderness, and destruction of synovial joints, leading to severe disability and premature mortality. Ultrasound (US) evaluations are more sensitive techniques to identify synovitis than clinical examination Objectives: To find the relationships between ultrasonography changes and pro-inflammatory cytokines levels in patients with rheumatoid arthritis Methods: The study included 36 patients (28 females; median age 53.9 [47; 61] y) with early RA (median duration 8.0 [5.0; 11.5] mo; DAS28 5.6 [4.8; 6.4]; positivity for rheumatoid factor (RF+) was established in 89%; positivity for anti-cyclic citrullinated peptide antibody (ACCP +) - in 92%). All patients were administered methotrexate (MTX) and/or biologic therapy in accordance with the treat-to-target concept (REMARCA study). Serum cytokine concentrations were measured using the xMAP multiplexing technology at baseline, in 12 and 24 weeks after initiation of therapy. Ultrasound with gray scale (GS) and power Doppler (PD) were performed at baseline, in 12, 24 and 52 weeks after initiation of therapy. Eight joints of the clinically dominant hand and foot were sonographically evaluated. The wrist, MCP2 and MCP3, PIP2 and PIP3 joints, as well as MTP2 and MTP5 joints of the clinically dominant side, were sonographically examined in a standardized manner according European League Against Rheumatism (EULAR) guidelines. ESAOTE MyLabTwice and GE Logiq 9 US machines with 13-18 MHz-transducter were used. GS and PD changes at the end of follow up period (52 mo) were used as end points in our study. Absolute levels and magnitude of change were analyzed Results: We found significant correlation between PD findings and levels of pro-inflammatory cytokines at baseline: IL-1b (r=0.34, p <0.02), IL-6 (r=0.42, p <0.005), and also as with CRP (r=0.38, p <0.01). GS findings at baseline correlated only with CRP levels (r=0.61, p <0.0001) and DAS-28 (r=0.32, p<0.04). At Week 52 DAS28 remission rate was 53%, but ultrasound remission criteria were found only in 4 patients. The correlation was found between PD-changes and baseline IL-6 levels (r=0.44, p <0.01), as well as with changes in IL-6 levels following first 12 weeks of therapy (r=0.45, p <0.01). Of note, the baseline IL-6 levels in patients with negative baseline PD-signal dropped significantly by the end of FU 52 mo period as compared to pts with baseline positive PD- signal (38.7 [19.2;59.6], vs 75.2 [37.9;101.7]. GS dynamics during all treatment period (from baseline to 52 weeks) correlated only with IL-6 levels dynamics by Week 12 (r=0.53, p <0.001). No correlation was found between ultrasound findings (GS and PD) and levels of other pro-inflammatory cytokines (IL-7, 12, 15 and MIP-1α). Similarly correlation was not established between dynamics in ultrasound (GS and PD) findings and DAS-28 scores at the end of treatment period, except for relationship between DAS-28 at baseline and PD-changes during all treatment period (from baseline to 52 weeks) (r=0.37, p <0.03) Conclusions: IL-6 level seems to be the marker of ultrasound synovitis at baseline and during follow-up. Continuously elevated IL-6 levels are usually associated with persistence of US inflammatory signs Disclosure of Interest: None declared